MiR-381-3p/RAB2A axis activates cell proliferation and inhibits cell apoptosis in bladder cancer - Sun, Xiaolu; Hu, Xiufang; Wang, Xiangtao; Jiang, Xianzhou (Cellular and Molecular Biology, 2020)
Acting as a really common cancer in the world, bladder cancer has taken many people's life away. MiRNAs and mRNA have been reported can regulate the expression of cancers. In this study, the role of RAB2A and miR-381-3p was fully studied in bladder cancer. qRT-PCR assay probe the expression of RAB2A and miR-381-3p in bladder cancer cells. Meanwhile, colony formation assay, EdU assay, flow cytometry analysis, JC-1 assay and western blot assay were implemented to detect the progression of bladder cancer cells. Silenced RAB2A could reduce the cell proliferation of bladder cancer, and activate the apoptosis. Meanwhile, miR-381-3p could bind to RAB2A in bladder cancer cells and overexpressed miR-381-3p could inhibit the progression of bladder cancer cells. MiR-381-3p/RAB2A axis activates cell proliferation and inhibits cell apoptosis in bladder cancer.